CTBP1 links metabolic syndrome to polycystic ovary syndrome through interruption of aromatase and SREBP1 - Yue Kong; Guang Yang; Xu Feng; Zhaodong Ji; Xiaoling Wang; Yang Shao; Jiao Meng; Guidong Yao; Chunxia Ren; Gong Yang (Communications Biology, 2024)
Abstract Some patients with polycystic ovarian syndrome (PCOS) suffered from metabolic syndrome (MetS) including dyslipidemia, hyperinsulinism, but the underlying mechanism is unclear. Although C-terminal Binding Protein 1 (CTBP1) is a transcriptional co-repressor frequently involved in hormone secretion disorders and MetS-associated diseases, the role of CTBP1 in PCOS is rarely reported. In the present study, we found that CTBP1 expression was significantly elevated in primary granulosa cells (pGCs) derived from the PCOS with MetS patients and was positively associated with serum triglyceride, but negatively correlated with serum estradiol (E2) or high-density lipoprotein. Mechanistic study suggested that CTBP1 physically bound to the promoter II of cytochrome P450 family 19 subfamily A member 1 (CYP19A1) to inhibit the aromatase gene transcription and expression, resulting in the reduced E2 synthesis. Moreover, CTBP1 interacted with the phosphorylated SREBP1a at S396 in nuclei, leading to the FBXW7-dependent protein degradation, resulting in the reduced lipid droplets formation in pGCs. Therefore, we conclude that CTBP1 in GCs dysregulates the synthesis of steroid hormones and lipids through suppression of aromatase expression and promotion of SREBP1a protein degradation in PCOS patients, which may offer some fresh insights into the potential pathological mechanism for this tough disease.